Establishment of an efficient primary callus induction for embryogenic potential of Coffea arabica - Arimarsetiowati, Rina; Daryono, Budi Setiadi; Astuti, Yohana Theresia Maria; Semiarti, Endang (Indonesian Coffee and Cocoa Research Institute, 2022)
Coffea arabica L. is a species of coffee that contribute for more than seventy percent of world coffee production. Various attempts have been made to obtain large quantities of planting material through propagation in vitro somatic embryogenesis technology. The objective of this experiment was to evaluate the effect of different plant growth regulators (PGRs) on callus induction (indirect somatic embryogenesis) in AS2K clone of Arabica coffee. Mother plants of Arabica coffee were established in coffee experimental field of Indonesian Coffee and Cocoa Research Institute at Andung Sari, Bondowoso, East Java, Indonesia (-7Ëš55'' ' S, 113Ëš41'' ' E) at an altitude of 1380,1 m dpl. Leaf explants were cultured on a half-strength Murashige and Skoog (MS) medium supplemented with various concentration (1.0, 2.0, 3.0 mg/L) of 2,4-D and (1.0, 2.0, 3.0 mg/L) thidiazuron in combination with 1.0 mg/L BAP. All the experiments were organized in completely random design (CDR) and repeated three times, each using minimum seven replicates (a total of 21 explants per treatment). The morphologycal and histological analysis of the different types of callus were observed. The percentage of callus formation was recorded every two weeks until eight weeks. The highest percentage of callus formation (almost 60%) was in medium containing 1 mg/L 2,4-D dan 1 mg/L BAP. Morphological and histological studies prove that the callus has a friable and embryogenic texture and begins to develop various stages of somatic embryo formation, starting with the globular, heart, torpedo and cotyledonary phases.